1997
DOI: 10.1111/j.1540-6288.1997.tb00440.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Method of Payment and the Type of Offer on Target Returns in Mergers and Tender Offers

Abstract: This paper re-examines the effects of the method of payment and type of offer on target abnormal returns around the takeover announcement, controlling for the target firm's institutional ownership. Previous studies suggest the difference in announcement-period target returns between cash offers and stock exchange offers can be explained by the difference in capital gains tax liabilities of the target shareholders and/or the difference in the information effect of the method of payment. The empirical results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…They found that the abnormal return of bidding firms on the announcement day were -1.3% for stock exchange and -0.8% for cash offers. Suk and Sung (1997) looked at the effects of method of payment, form of acquisition and type of offer on target firms' abnormal returns around the takeover announcement. They showed that there was no difference in premiums between a stock offers and a cash offers.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the abnormal return of bidding firms on the announcement day were -1.3% for stock exchange and -0.8% for cash offers. Suk and Sung (1997) looked at the effects of method of payment, form of acquisition and type of offer on target firms' abnormal returns around the takeover announcement. They showed that there was no difference in premiums between a stock offers and a cash offers.…”
Section: Introductionmentioning
confidence: 99%
“…Method of payment is extensively studied in the M&A literature. Jensen and Ruback (1983), Huang and Walkling (1987), and Suk and Sung (1997) find that target firms earn significantly higher abnormal returns in cash offers than in stock offers. On the contrary, Leeth and Borg (2000) find lower target firm gains from cash offers than stock offers by examining the 1920s merger wave.…”
Section: Hypothesesmentioning
confidence: 98%
“…If the method of payment is regarded as a reflection of the acquiring managers' views of the stand-alone value of their own company (Draper and Paudyal, 1999), then a stock offer may also carry an 'information effect' (Suk and Sung, 1997), signalling to the market that the bidding firm believes its own stock to be overvalued, or is uncertain as to the potential synergies arising from the merger. Under this signalling theory, a share bid alerts investors to pre-existing mispricing and therefore causes a share price reaction to correct misvaluation.…”
Section: Earnings Management and Bid-announcement Returnsmentioning
confidence: 99%